Effect of resistant starch type 2 on inflammatory mediators: A systematic review and meta-analysis of randomized controlled trials. (January 2021) - Haghighatdoost, Fahimeh; Gholami, Ali; Hariri, Mitra
Highlights: Resistance starch type II passes to the large intestine in undigested form and can be fermented by gut microbiota. Colonic fermentation of resistance starch improves the growth of some useful bacterial. A meta-analysis conducted on randomized clinical trials which assessed resistance starch effect on inflammatory mediators. Eight randomized clinical trials included in systematic review and meta-analysis. The overall effect illustrated no significant change in serum levels of c-reactive protein (CRP), interlukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) in intervention group compared with the control group. Abstract: Background: Inflammation is the main cause in the development of chronic diseases. The enhancement of pro-inflammatory factors, such as tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), and high-sensitivity C-reactive protein (hs-CRP) is the main risk factor in chronic diseases. Resistant starch type 2 (RS2) is non-gelatinized granules which their enzymatic hydrolysis is very low. RS2 might be able to reduce inflammatory mediators, therefore; our aim for this study was indicating RS2 effects on inflammatory mediators such as IL-6, TNF-a, and CRP among healthy and unhealthy subjects. Methods: Articles which assessed RS2 effect on IL-6, TNF-α, and hs-CRP were found by advanced search methods. Electronic databases including Google scholar, ISI web of science, SCOPUS, and PubMed, were searched up to October 2019. Treatment effect was the mean difference between changes in serum levels of inflammatory biomarkers in each arm of the clinical trials. To pool the effect of resistant starch on inflammatory biomarkers, we used random effects model. Results: We included eight articles in systematic review and meta-analysis. The overall effect illustrated no significant change in serum levels of hs-CRP, IL-6, and TNF-α in intervention group compared with the control group (WMD: -7.18 pg/mL, 95% CI: −27.80, 13.45; P = 0.495, I 2 = 100.0%, WMD: -0.003 pg/mL, 95% CI: −0.07, 0.06; P = 0.919, I 2 = 98.1%, WMD: -0.003 pg/mL, 95% CI: −0.004, -0.001; P < 0.0001, I 2 = 98.0% respectively). Conclusion: In conclusion, we found that RS2 could not reduce inflammatory mediators, but we still need more RCTs with longer intervention duration, higher dose, and studies in different countries.